Land Use Change on the Golden Triangle Area, Kuningan, South Jakarta - Annisa Fathaniah Latala; Rahel Situmorang; Herika Muhammad Taki (REKA RUANG, 2022)
Jakarta is a metropolitan city with high-rise buildings (apartemens, boarding houses, shopping centers – trading facilitites), especially in the Kuningan Golden Triangle area surrounded by office buildings, trade and service facilities, and mixed-use development which is controlled by development with a building intensity exceeding 100,000 m2. The purpose of this study is to identify changes in land use RW 07 area, Karet Kuningan, Jakarta Selatan from 2002 – 2021. The method used is descriptive quantitative, while data collection uses interview, field observations, documentation, and secondary data from goverment agencies. Such as the DKI Jakarta Departement of Human Settlements. The results of this study indicate that the changes that occur in the study area are: inappropriate land use, changes in building fuctions, and compatibility of KDB, KLB, and KDH at the study location. This study expected to be input for local goverments, especially DKI Jakarta, to re-evaluate existing regulations with field conditions and to improve the revision of the 2030 RDTR, especially in DKI Jakarta area.